Employing the power point program in developing the skills of students in the Department of Art Education Graphic material (Journal of the College of Basic Education, 2022)
The Department of Art Education is one of the scientific departments in the College of Fine Arts, University of Baghdad. It aims to prepare and qualify students for the profession of teaching art education in secondary schools. Its content has two sides, one is cognitive and the other is skillful, and graphics are one of the important materials in the student’s educational life.